Autonomic nervous system indices of player readiness during elite-level rugby union game-week microcycles - Grainger, A.; Heffernan, S.; Waldron, M.; Sawczuk, T. (The Journal of Strength and Conditioning Research, 2022)
Elite-level rugby union (RU) is a high-intensity contact sport that involves large training and match volumes across a season, which can lead to postmatch fatigue. Autonomic nervous system (ANS) regulation and perceived fatigue have been suggested to relate to measures of training and match load in RU. However, there have been no studies to assess specific ANS variables in elite RU during in-season microcycles. Player readiness during game-week microcycles was measured via heart rate variability (HRV) indices, direct current potential and self-reported well-being among 13, elite, male RU players. To enable comparison, data collection days were categorized in relation to their proximity to match day, ranging from match day minus 3 (MD - 3), to match day plus 3 (MD + 3). Differences between match days were evaluated using general linear models and Cohen's d effect sizes. There were significant differences between MD and MD + 1 for ANS indices (RMSSD p = 0.04, d = -0.66, 95% CI 0.11-1.20; the standard deviation of NN intervals p = 0.04, d = -0.66, 95% CI 0.12-1.20; total power p = 0.05, d = -0.65, 95% CI 0.11-1.20) and wellness measures (readiness p = 0.18; d = -2.33, 95% CI, 1.54-3.13; energy p = 0.02; d = -2.24, 95% CI 1.44-3.03; soreness p = 0.00; d = -2.42, 95% CI 1.63-3.23). Match day plus 3 effects were significantly greater than MD + 1 in several ANS responses, with wellness recovering at a slower time-course than ANS responses. Measures of HRV are dysregulated postmatch, but based on their rapid recovery thereafter, using HRV to assess readiness of elite-level players in RU across a weekly microcycle could be limited and requires further investigation.